2022
DOI: 10.1007/s12520-022-01619-x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal distances and cultural effects in the spread of the Neolithic along the northern Mediterranean coast

Abstract: We estimate a spread rate of 7.5–10.6 km/year for the Neolithic expansion along the northern shore of the western Mediterranean. Comparing to theory and numerical simulations of demic-cultural waves of advance, we find that the length of coastal jumps was $$240\le \Delta \le 427$$ 240 ≤ Δ ≤ 427 km. We also derive what we believe are the first analytical equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The loosely connected Impressa nodes may reflect this pioneer, fragmentary, and small-scale peopling event. The low degree of transformation observed during this spatially fragmented pioneer phase is seen as resulting from the process of long-distance maritime displacement [56,[83][84][85] and exploratory behavior [86]. This long-distance connection, highlighted by the higher Impressa mean similarity radius, may reflect these maritime displacements, compared to later periods when the smaller-scale inland dispersions of bigger communities is more likely [83,87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loosely connected Impressa nodes may reflect this pioneer, fragmentary, and small-scale peopling event. The low degree of transformation observed during this spatially fragmented pioneer phase is seen as resulting from the process of long-distance maritime displacement [56,[83][84][85] and exploratory behavior [86]. This long-distance connection, highlighted by the higher Impressa mean similarity radius, may reflect these maritime displacements, compared to later periods when the smaller-scale inland dispersions of bigger communities is more likely [83,87].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that during the Early Neolithic human communities were highly connected and mobile, with well-developed large-scale circulation networks [51][52][53][54] that favoured both cultural and demic diffusions. Additional studies have evidenced that each mechanism acted to a different extent across Europe [55,56], although these interactions did not uniformly affect the various elements of the first farmers' material culture. Nevertheless, by comparing two proxies with an exclusively symbolic function, pottery decorations and personal ornaments, distinct patterns of interaction among early farming communities can be identified.…”
Section: Research Objectivesmentioning
confidence: 98%